(untitled) (Bangladesh Journal of Agriculture, 2022)
Tissue culture has long been recognized as an ideal experimental paradigm for studying the mechanisms governing plant cell growth, division, and physiological and biochemical processes. The present investigation was undertaken to establish a standard method for callus induction, shoot and root regeneration of rose at Genetic Engineering and Biotechnology Laboratory, University of Rajshahi, Bangladesh in 2010. Shoot tip and nodal segments were used as experimental materials excised from field grown plants for callus induction. The direct shoot was observed from both shoot tip and nodal segments for shoot regeneration. In vitro regenerated shoot cuttings were used for root regeneration. Proper manipulation of auxin (2, 4 -D and NAA) was used to induce callus from different explants. Different growth regulators (BAP, KIN and GA3) were casted-off in combination for shoot regeneration and proliferation. Again, different concentrations of auxins (IBA, NAA, and IAA) were applied for root initiation. Among the hormonal supplements used, 2, 4 -D was found best in all respect of callusing response for all types of explants. The highest percentage (90%) of callus induction was observed in media having MS (Murashige and Skoog) + 4.0 mg/L 2, 4 -D. In case of shoot regeneration, 100% of cultured explants regenerated shoot in media with MS + 2.0 mg/L BAP + 0.5 mg/L KIN. While, 2.0 mg/L BAP + 0.5 mg/L KIN + 0.1 mg/L GA3 induced 100% shoot proliferation. Moreover, for root induction, ½ MS + 1.0 mg/L IBA + 1.0 mg/L NAA proved to be the best (80%) from in vitro regenerated shoot cuttings, and the highest mean number of roots was 5.0. Rooted shoots were acclimatized and successfully established in a natural condition where 60% of the transplanted plants survived. Bangladesh J. Agri. 2022, 47(1): 66-74